2009
DOI: 10.1007/s10802-009-9318-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Lifetime Depression with Trauma Exposure, Other Environmental Adversities, and Impairment in Adolescents with ADHD

Abstract: Depression is a common, potentially devastating comorbidity in youth with attention-deficit/hyperactivity disorders (ADHD). Various environmental adversities are well-described as correlates of depression in general pediatric populations, but not in youth with ADHD. In 104 adolescents with ADHD, we examined potential environmental correlates of lifetime depression, including trauma exposure, recent negative life events and current parent-child conflict, along with current and past ADHD severity and current imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…Moderate to high rates of comorbid ADHD and mood disorders, ranging up to 75%, have been found in youth (Bauermister et al, 2007Biederman, Newcorn, Spirch, 1991Daviss, 2009;Elia, Ambrosini & Wade, 2008 research suggests increased rates of mood disorders (Biederman, et al, 2008;Green et al, 1997;Fisher, et al, 2002;Biederman, et al, 2006;Monuteaux, et al, 2007) as well as depressive symptoms (Hinshaw et al, 2006;Lahey et al, 2007;Lee et al, 2008) in youth diagnosed with ADHD in comparison to non-ADHD youth.…”
Section: Primary Aim 1: To Compare Youth With and Without Adhd On Depmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate to high rates of comorbid ADHD and mood disorders, ranging up to 75%, have been found in youth (Bauermister et al, 2007Biederman, Newcorn, Spirch, 1991Daviss, 2009;Elia, Ambrosini & Wade, 2008 research suggests increased rates of mood disorders (Biederman, et al, 2008;Green et al, 1997;Fisher, et al, 2002;Biederman, et al, 2006;Monuteaux, et al, 2007) as well as depressive symptoms (Hinshaw et al, 2006;Lahey et al, 2007;Lee et al, 2008) in youth diagnosed with ADHD in comparison to non-ADHD youth.…”
Section: Primary Aim 1: To Compare Youth With and Without Adhd On Depmentioning
confidence: 99%
“…Moderate to high rates of comorbidity between ADHD and mood disorders in youth have been established in cross-sectional studies including both community (Anderson, Williams, McGee & Silva, 1987;Angold, Costello & Erkanli, 1999;Bauermeister et al, 2007;Bird, Canino, Rubio-Stipec, Gould, Ribera, Sesman et al, 1988;Blackman, Ostrander & Herman, 2005) and clinical samples (Daviss, 2009;Elia, Ambrosini & Wade, 2008;Milberger, Biederman, Faroane, Murphy & Tsuang, 1995;Souza, Pinheiro, Denardin, Mattos, & Rohde, 2004). Cross-sectional studies of community-based samples suggest that the co-occurrence rates of Attention Deficit Disorder (ADD, DSM-III-R, American Psychological Association, 1987) and/or Attention Deficit/Hyperactivity Disorder (ADHD, DSM-IV, American Psychological Association, 2000) and mood disorders range from 0% (McGee et al, 1990) to 75% (Biederman, Newcorn, Spirch,1991) (for reviews see Angold & Costello, 1993Jensen, Martin & Cantwell, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier study found that youth with ADHD had significantly more total, child-dependent, and child-independent ALEs than healthy controls, adjusting for age, gender, and pubertal status (Tillman et al 2003). The second, which was exclusively in a sample of youth with ADHD, reported that there were significant univariate correlations between lifetime depression and both child-dependent and child-independent ALEs, but only child-independent ALEs remained a significant correlate of lifetime depression after controlling for the effects of ADHD severity, comorbid externalizing disorders, age, and female gender (Daviss et al 2009). Two longitudinal studies have examined environmental adversities as predictors of the subsequent course of ADHD (Biederman et al 1996;Kessler et al 2005), but only the earlier study suggested that ALEs contribute to the persistence of ADHD diagnosis.…”
Section: Introductionmentioning
confidence: 96%
“…This study's findings suggest the need to control for the effects of other comorbidity when assessing the relationship between a particular psychiatric diagnosis and ALEs. Only two studies have examined the associations of ADHD diagnosis or ADHD severity with ALEs, taking into consideration whether such events were likely dependent on the child's behaviors (Tillman et al 2003;Daviss et al 2009). The earlier study found that youth with ADHD had significantly more total, child-dependent, and child-independent ALEs than healthy controls, adjusting for age, gender, and pubertal status (Tillman et al 2003).…”
Section: Introductionmentioning
confidence: 99%